Work engagement among employees at Kulim (Malaysia) Berhad - Nurfadzidah, Azhar (2019)
Having highly engaged employees are critical for every organization. This is because highly engaged employees are more customer focus, more creative, take less sick leave, care about the future of the organization, put in greater effort in achieving organization objectives, feel proud with the organization that they work for, are inpired to do their best and motivated to deliver their organization’s objectives. Even though organization realized the importance of having highly engaged employees, it is one of their top challenges.Thus, this study is conducted with the intention to capture factors that might influence work engagement among employees. The study examines the direct relationship between ethical climate, ethical leadership, psychological empowerment, employee values and work engagement. A total of 181 questionnaire were distributed online through google form format to respondents at Kulim (Malaysia) Berhad after permission was granted by the company. Out of 181 questionnaire distributed, only 177 questionnaire were returned, representing a response rate of 97.79%. However, 156 were usable for further analysis, after deleting the outliers cases. Hypotheses for direct effect were tested using multiple regression analyses. Results showed that ethical climate, ethical leadership, psychological empowerment and employee values were positively related to work engagement. The findings indicate that work engagement among employees can be enhanced by creating an ethical work environment, practicing ethical leadership style, giving the opportunity to employees to actively invlove with their work, and focusing on positive values like fairness.